Analysis of Factors That Influence the Implementation of SAK EMKM - Kurniawan, Elan; Mardiyah, Winda; Juardi (Indonesian Scientific Publication, 2024)
This research aims to analyze the influence of Socialization of Micro, Small and Medium Entities (EMKM) and Accounting Understanding on the Implementation of SAK EMKM. The population in this research is MSMEs in the culinary sector in the Bogor Regency area. This research uses primary data which is measured using a Likert scale. The data collection method was carried out by distributing questionnaires using Google Form. Sampling was carried out using purposive sampling and the total sample was 61 respondents. Analyzed using SmartPLS Version 3.2.9. The research results show that Socialization of Micro, Small and Medium Entities (EMKM) and Accounting Understanding have a positive and significant influence on the Implementation of SAK EMKM, this proves that the consistency of socialization of understanding of accounting skills in accordance with SAK EMKM can expand reach to other MSME actors. With the socialization of EMKM and understanding of accounting, it will increase the application of SAK EMKM, this can actually help the implementation of SAK EMKM to be of higher quality, one of the proofs of success in getting a KUR loan is because the financial reports are well structured and correct.